BioMEMS and Nanotechnology III 2007
DOI: 10.1117/12.765011
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave device based wireless passive microvalve for microfluidic applications

Abstract: There are vast advantages in the realisation of a SAW device based microvalve in Micro Electro Mechanical Systems (MEMS) and Nano Electro Mechanical Systems (NEMS) such as secure, reliable and low power operation, small size, simplicity in construction and cost effectiveness. In this paper, a Surface Acoustic Wave (SAW) based microvalve that generates micro actuations for microfluidic and similar applications is presented. The microvalve is batteryless and can be actuated wirelessly. The security of the device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…1 As it was presented in authors' previous work, 1, 3 only the effect of the output IDT is considered for the FEA, instead of incorporating the whole SAW device.…”
Section: Fea and Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As it was presented in authors' previous work, 1, 3 only the effect of the output IDT is considered for the FEA, instead of incorporating the whole SAW device.…”
Section: Fea and Simulation Resultsmentioning
confidence: 99%
“…1 Based on the previous work carried out by the authors 1,3,4 it is been demonstrated that the required wireless and batteryless actuation for a microfluidic device is achievable using a fully passive system. Initially, the micropump structure is designed by integrating a SAW device and a micropump chamber, which causes the microfluidic modulation.…”
Section: Microfluidic Devices For Drug Deliverymentioning
confidence: 99%
“…Figure 7 shows the mid-beam and the quarterbeam displacement variation over the time (250-time-periods). Based on authors' previous work, it was shown that beam displacements up to 2 μm can be achieved using SAW device based actuation [16]. After carrying out a few different transient analysis simulations with different end times and comparing the obtained transient displacements with the static displacements achieved, it is proven even [17] after 250-time-periods still the dynamic displacement is not showing any periodic nature but in the process of gaining more displacement.…”
Section: Transient Analysismentioning
confidence: 90%
“…The electric potential at x 3 = h is zero because of the conductive plate. Using this condition, B can be eliminated from (16) and can be rewritten as…”
Section: Mechanical Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation